Fruit and seed biometry of Butia capitata (Mart.) Beccari (Arecaceae), in the natural vegetation of the North of Minas Gerais, Brazil - Moura, Roberto Cardoso de; Lopes, Paulo Sergio Nascimento; Brandão Junior, Delacyr da Silva; Gomes, Janaína Gonçalves; Pereira, Maurício Ballesteiro (Biota Neotropica, 2010)
The fruit "coquinho-azedo" (Butia capitata (Mart.) Beccari), has a great social and economic importance to the communities located close to its distribution areas. Biometric characteristics of fruit and seed are important for the distinction of species, for the formation of more uniform seed lots, for the studies of dispersion and seedling establishing. Thus, the aim of this work was to determine and correlate main fruit and seed biometrical characteristics of the "coquinho-azedo" in order to provide information on the productive and economic potentialities of this species. In this experiment, 2.050 mature "coquinho-azedo" fruits were collected at 41 plants. The evaluated characteristics had been: the longitudinal diameter and the equatorial diameter of the fruits, the average the fresh mass of the fruit, the fresh and dry mass and the average humidity of the pulp (epicarp + mesocarp), the fresh mass of the pyrene (endocarp + seed), the number of seeds, and also the percentage of pulp e pyrene of the fruit. An average longitudinal diameter of 26,87 mm (± 2,77), an equatorial diameter of 21,10 mm (± 1,67) and an fresh average fruit mass of 8,02 g (± 1,73) were obtained. The fruit pulp represents, in mass, approximately 80% of the fruit. The mass and diameter of the fruit showed significant and positive correlations with most valued characteristics, suggesting that fruits of bigger size and mass have heavier pulp and pyrene and more seeds per fruit. In 99% of the fruit examined only one seed was not is observed parthenocarpic fruits or more than two seeds fruits.